2018
DOI: 10.2147/nss.s168841
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of potential objective and subjective daily indicators of sleep health in normal sleepers

Abstract: PurposeWhile the concept of “sleep health” has only recently been defined, how it relates to both subjective and objective sleep parameters is yet to be determined. The current study aimed to identify potential indicators of poorer sleep health, from subjective and objective daily sleep characteristics, in normal sleepers.Participants and methodsEighty-three individuals aged 18–65 years with no history of sleep disorders, chronic physical or psychiatric illnesses, or substance misuse were recruited from the No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In summary, we deeply appreciate the letter by Sharman et al 1 but hope to have clarified all issues raised. As reported by the authors' research group earlier, 5 differences between selfreported and objective sleep measures are common, even in healthy individuals. We expand on this topic by reporting effects of different types of sleep disorders on sleep misperception.…”
supporting
confidence: 54%
“…In summary, we deeply appreciate the letter by Sharman et al 1 but hope to have clarified all issues raised. As reported by the authors' research group earlier, 5 differences between selfreported and objective sleep measures are common, even in healthy individuals. We expand on this topic by reporting effects of different types of sleep disorders on sleep misperception.…”
supporting
confidence: 54%
“…Besides, we found a low correlation between PSQI and sleep efficiency. A non-significant association between subjective and objective sleep quality was found in previous studies ( 56 , 57 ) in which psychological and physical discrepancies were also evident. Subjective sleep quality seems to be affected by psychological health ( 56 ); our DSEM finding that PSQI did not predict the PHQ or GAD score could be viewed as an extension of such results.…”
Section: Discussionmentioning
confidence: 53%
“…The subjective information given by the participants in the questionnaires did not correlate to the PAM data. This is of further interest since subjective parameters provided by questionnaire are inconstant [1] in comparison to PSG sleep parameters. A recent study showed that the majority of objective sleep parameters appear not to be sensitive to sleep health status in normal sleepers [10].…”
Section: Discussionmentioning
confidence: 99%
“…The interest in sleep and sleep quality has grown strongly among the population in recent years. Sleep is not only essential for the optimal performance of physical, cognitive and emotional processes but also a vital biological determinant of everyday health and well-being [1]. For athletes in particular, the connections between memory consolidation, newly learned training techniques (training optimization) and increased competitive performance through restful sleep seem to be of importance and are making sleep quality increasingly the focus of new research questions [2].…”
Section: Introductionmentioning
confidence: 99%